Evaluation of Mechanical Properties and Volatile Organic Extractable to Investigate LLDPE and LDPE Polymers on Final Packaging for Semisolid Formulation - Arianna Cecilia Cozzi; Benedetta Briasco; Enrico Salvarani; Barbara Mannucci; Filippo Fangarezzi; Paola Perugini (MDPI AG, 2018)
Plastic material is used for a wide variety of commercial packaging due to being inexpensive, lightweight, and due to its resistance. In pharmaceutics, container-content compatibility studies are required for product authorization. Many guidelines and publications are available; however, the information is often only related to the raw materials used to produce packaging. During the manufacturing process, substances can be added to improve the product characteristics and performance, resulting in a processed material that is considerably different from the unprocessed material. In this study, the mechanical properties of low-density polyethylene (LDPE) and linear low-density polyethylene (LLDPE) specimens fabricated according to standard ISO 527 and specimens fabricated with the same materials, but obtained from final packaging, were evaluated. Furthermore, we examined the interaction between a semisolid formulation and LLDPE and LDPE as a final packaging, by subjecting two samples to accelerated degradation testing. Then, mechanical properties and volatile organic extractable were evaluated. Simulated solar radiation did not induce changes in the packaging mechanical properties and no extracts were detectable. The thermal shock strongly influenced the mechanical behavior, and interactions between packaging contents were identified. The present work underlines the difference between analyzing the standard ISO specimens versus samples obtained from final packaging in order to evaluate the packaging under real use conditions. An evaluation on the final packaging, instead on standard specimens, can provide information about the plastic material after the manufacturing process and the interaction between packaging and content.